PENGALIHAN KREDITUR MELALUI CEASIE （STUDI KASUS PADA KOPERASI SIMPAN PINJAM INDOSURYA ） - Sri Eni Julianita Koto (Universitas Harapan Medan, 2021)
The state of liquidation of each bank and non-bank financial institution is strongly affected by social and economic conditions, both on a national and international scale. In order for lending (loans) to continue to run, it is known that the accounts receivable transfer agency is known as cessie. Based on Article 613 of the Civil Code, it is stated that the delivery of receivables in the name and other bodily objects is carried out by making an authentic deed or deed under the hands of which the rights to property are delegated to others. The delivery of these receivables has no effect on the debtor before delivery is notified and approved in writing or acknowledged by the Debtor / Borrower. The existence of an authentic deed or underhand deed is needed as a way of transferring or transferring ownership rights over the receivables in question from the creditor to a third party. The role and authority of a Notary in the making of cessie documents, as regulated in the notary office law, namely